CUSTOMS AFFAIRS IN THE CONTEXT OF PART 1 OF ARTICLE 67 OF THE CONSTITUTION OF UKRAINE - Nazarko, Artem (Collection of scientific papers «ΛΌГOΣ», 2023)
Undoubtedly, the Constitution of Ukraine is decisive in the legal regulation of customs affairs. That is, it forms the highest level [1]. The Constitution of Ukraine has the highest legal force, and laws and other normative legal acts must be adopted on its basis; they must correspond to it [p. 2 art. 8; 1]. Constitutional norms are norms of direct effect; that is, they are subject to direct application in practice when solving specific issues, including in the field of customs affairs [p. 3 art. 8; 1] in connection with which the Constitution is the basis for further legislative and other rule-making activities.